Balancing Cultures: Analyzing the Adaptation of English Language Teaching Materials to suit the ESL Context in Sri Lanka - Rajarathna, Y.G.A.D.S.; Weerasinghe, W.M.N.C.; Karunarathne, H.M.M.S. (University of Jaffna, 2025)
Language is inseparably linked to culture, and teaching English as a Second Language (ESL) often involves navigating the cultural dimensions embedded in the language. In the Sri Lankan context, localizing English language teaching materials has become common practice, but this process often filters out cultural aspects central to the authentic use of English, such as inclusivity, gender roles, and global perspectives. This disconnection can limit students’ exposure to diverse worldviews and hinder their readiness to engage in a globalized society. This study involved a qualitative discourse analysis approach to analyzing lesson material used to teach compulsory English courses at the Faculty of Arts, University of Peradeniya, using cultural theories related to ESL. These lessons were chosen because they are utilized in teaching the compulsory English courses for first-year and second-year undergraduates, serving as the foundation for successful academic performance. It examined the practicality of finding a middle ground by incorporating both localized and original texts in English lesson materials in order to provide the learners with both local and global experience. The research analyzed how this approach is practiced in the Sri Lankan ESL context and its implications for bridging cultural gaps in language instruction. The findings revealed the benefits of integrating localized and original texts, emphasizing the need for a balanced approach that accommodates students’ cultural identities while providing exposure to global perspectives. In conclusion, by critically evaluating the textualization and implementation of such practices, this study highlights their potential to support linguistic competence and cross-cultural understanding in ESL learners, preparing them to navigate the complexities of a globalized world.
Keywords: Localizing; English language teaching; English as a second language